PENGEMBANGAN POTENSI WISATA GENTAN MELALUI PENULISAN SEJARAH LOKAL - Umi Yuliati; Fatahillah Irsyaf; Fajar Maulana; Intan Dian; Isabel Agve; Jovina Putri; Khoirroh Amalia; Kinanti Putri; Lorient Marccelita; Rizka Adinda; Zakiyatun Nur (Jurnal Abdi Insani, 2023)
Gentan Village is a tourist village known as Gentan Geopark Village. The charm of tourism owned by Gentan Village includes natural, cultural, historical, and culinary potential to be a special attraction for tourists. Gentan Geopark Village began to be developed in 2019 by raising the concept of a natural tourist village derived from natural heritage formed millions of years ago. In one Gentan Geopark Village destination, there are five tourist destinations that can be directly visited, namely Platar Ombo, Mount Sepikul Segendong, Batu Seribu Tourism, Sendang Lele, and Embung Pacinan. Gentan Village also has cultural heritage in the form of folklore in the form of myths and legends that need to be developed to support tourist interest. This service aims to introduce geotourism in Gentan Village which contains folklore that not many people know about to add cultural and historical insights. This folklore aspect can be used as a promotional event for tourism by selling interesting previous stories. The methods used in this service are observation, discussion, and interview. Starting with making observations to see the conditions around tourist destinations in Gentan Village, followed by discussions with village officials and several local residents to discuss what problems are happening in Gentan Village tourist destinations and their solutions. The last method is an interview with village elders to explore the folklore that develops in the Gentan Village geotourism area which will be poured into the Gentan Village tourism profile video and the Gentan Geopark Village Pocket Book. In addition, the service activity is also in the form of optimizing the Instagram account of Gentan Geopark Village so that Gentan Village is able to take advantage of mass media to attract tourists.